Effect of cryoprotection on particle size stability and preservation of chitosan nanoparticles with and without hyaluronate or alginate coating - Abdulaziz Almalik; Ibrahim Alradwan; Mohd Abul Kalam; Aws Alshamsan (Elsevier, 2017)
The aim of the present study was to determine the effect of different cryoprotectants and their concentration on the physicochemical characteristics of chitosan nanoparticles (CS-NPs). The effect of coating of CS-NPs with hyaluronic acid (HA) and alginic acid (ALG) before and after lyophilization was also evaluated. The ionic gelation method was used for the preparation of NPs and six different types of cryoprotectants (sucrose, glucose, trehalose, mannitol, polyethylene glycol-2000, and polyethylene glycol-10,000) were investigated at 5%, 10%, 20%, and 50% concentration levels. Coating of CS-NPs with HA and their protection with high amount of cryoprotectants indicated better particle size stability. Samples that were lyophilized without cryoprotectants resulted in an increase in average size due to high agglomeration. All cryoprotectants with varying amount provided some sort of size stability for the NPs except for the PEG-10,000 which had no protective effect at higher concentrations. Sucrose and trehalose sugars were found to have the highest protective effect with HA coated and uncoated CS-NPs. In conclusion, using cryoprotectants along with surface coating, the CS-NPs could achieve the desired physicochemical characteristics for a prolonged duration.